Geobotanical classification of houseplants, ecology of main genera and species - Choriyev Jahongir Olimjon og’li; Qodirova Muxlisa Turg’unovna; Khurramova Mukhlisa Ikramovna (Genius Publishing Group, 2022)
Houseplants are ecologically pure plants that are widely used today for aesthetic pleasure. They are widely used in decoration. This article provides information on the origin of houseplants, their geobotanical classification, their growing conditions
Keywords: Houseplants; Kitab as-Saydana fit-t-tib; Hamsa; ampel plantse